Visual Outcome after Nd-YAG Capsulotomy in Posterior Capsule Opacification - , Niamatullah Kundi, Mohammad Younas Khan, Sanaullah Jan, Mohammad Naeem Khan, Shafqatullah Khan (Pakistan Journal of Ophthalmology, 2006)
Purpose: To find out the immediate visual outcome after performing Nd-YAG laser capsulotomy for posterior capsular opacification (PCO) in adults. Materials and Methods: After thorough prelaser assessment, Nd-YAG laser capsulotomy was carried out with Zeis VISULAS YAG II through Zeiss slit lamp under topical anaesthesia for 58 eyes with PCO in 58 patients. Postlaser visual acuity (VA) compared to preoperative VA was noted. Associated comorbidities were also noted. Results: Of the 58 patients, 39 (67.2%) were male and 19 (32.8%) were female. Nine (15.5%) were aphakic and 49 (84.5%) were pseudophakic. The average age was 52 years (Range 18 years to 83 years). The average time interval between cataract surgery and Nd-YAG laser capsulotomy was 23 months (2 months to 12 years). Capsular fibrosis (62%) was the predominant type of PCO. Elschnig’s pearls were present in 20.7% and capsular wrinkling found in 15.5%. All these capsulotomies were performed for optical purposes and the results were rewarding. The pre laser VA of more than 70% of eyes was 6/36 or below while 44.8% had VA of hand movements or finger count. Visual acuity of 6/18 or better was achieved in 60.2% of eyes while 12.0% recovered to 6/9 and 3.4% achieved 6/6. None of these eyes showed further deterioration in VA. Conclusion: Neodymium-YAG capsulotomy for PCO is rewarding procedure in adults and visual outcome is good. Comorbidities may reduce the better visual outcome.